Pathogenicity of Sclerotium rolfsii Isolates Causing Stem and Root Rot Disease of Cowpea Vigna unguiculata (L.) Walp and Management Using Trichoderma Species - Victor Ohileobo Dania; Enwongu Uso Henry (AGRIVITA, Journal of Agricultural Science, 2022)
Sclerotium rolfsii is a soil-borne pathogen causing stem and root rot disease with concomitant reduction in growth and yield of cowpea. Therefore, this study evaluated pathogenicity of S. rolfsii isolates and the management of root and stem rot disease using Trichoderma species. The isolates were obtained from cowpea rhizosphere and pathogenicity was determined using a susceptible cowpea genotype ITI0K–815-5 in an experiment arranged in a completely randomized design with four replications. In vitro and in vivo trials of Trichoderma spp. against a selected virulent isolate Sclerotium rolfsii (SR06) were conducted in the laboratory and screenhouse, respectively. All nine S. rolfsii isolates were pathogenic to the cowpea genotype, while isolate SR 06 was the most virulent with 85.56% infectivity rate. Treatments with T. virens and T. atroviride application reduced the disease incidences to 22.2% and 25.3%, respectively, compared to synthetic funguforce fungicide. Plants that were inoculated and treated with T. atroviride had significantly higher yield of 435 kg/ha than other treatments (p<0.037). Findings from this research encourages the incorporation of Trichoderma species in the integrated management of S. rolfsii pathogen and the incidence of stem and root rot disease in cowpea.